A percepção dos atores sociais da construção do conhecimento agroecológico: uma análise sobre a Política Nacional de Assistência Técnica e Extensão Rural e as Agriculturas Sustentáveis no Ceará - Pinheiro, Bruna Carolina Frazão Silva (2018)
Public policies aimed at modernization, based on the technology diffusion model, in which the Technical Assistance and Rural Extension (TARE) agent was a key piece for the process, favored the latifundio and intensified socioeconomic inequalities in rural areas, in which farmers were excluded from the process. The resumption of effective efforts to strengthen family agriculture and meeting the civil society organized demands, by a sustainable agriculture model, came with the National Policy on Technical Assistance and Rural Extension (PNATER) in 2003, which broke with the paradigm of TARE and focused on an TARE compatible with the concept of sustainable rural development based on agroecology, adoption of a participatory methodology and multidisciplinary approach, to build, together with farmers, agroecological production methods. Given this, it is important to inquire about the perception on PNATER of the social actors (development project managers, scholars, TARE technicians and peasants) from the agro-ecosystems of Ceará and organic and agro-ecological agricultures. The research is part of the project to create the Nucleus and Studies in Agroecology and Ecological Economics at the Center of Agricultural Sciences (CCA) of the Federal University of Ceará (UFC). In this research, Bardin's (1977) content analysis was applied on the interviews, taking as into account the theory of Röling and Jiggins (1998) on ecological knowledge system. The non-probabilistic sampling known as "snowball" was used in order to select the different study participants. Interviewees’ responses were analyzed with the aid of a matrix of categories that allowed capturing the social actors’ perception on agroecological knowledge construction. From the category matrix analysis, it was possible to verify a higher concentration of themes at the level of family and community agroecosystem and that the benefits perceived by the interviewees regarding the sustainable agriculture were individual and community. In this way, it is observed that actions in favor of organic and agroecological agriculture are basically in the first three levels of the ecological knowledge system (ecologically correct practices, learning and learning facilitation). The social actors’ focus was on production and trading consolidation. The first is due to the increase, diversification and seasonality of production, while the second focuses on the short trade channels, being local fairs and traders or the healthy products market in the Metropolitan Region of Fortaleza. The perception of the future about sustainable agriculture, agroecology and organic agriculture, were convergent, but differentiated in each group. Scholars were optimistic, but considered that there is a need for the development of alternative technologies for such models of agriculture, to ensure TARE and financial resources. The development project managers expressed the need to expand the market for organic and agroecological products, both from the point of view of demand and supply. Peasants, however, have made their own demands to continue with agroecological or organic practices. Regarding the perception on PNATER, only one of the interviewees, who was a scholar, cited PNATER, when addressing the differences between the types of TARE. Although all social actors spoke about TARE services, the differentiation between agroecological TARE and other forms of TARE, whether governmental or non-governmental, made clear that it is still necessary to consolidate TARE in Brazil, to increase the dissemination of PNATER, with regard to the policy institutionalization. All social actors, especially peasants, stressed the importance of TARE agents for the transition from the conventional model of agriculture to the sustainable agriculture model: organic and agroecological agriculture.